Insights into Duodenal Adenocarcinoma: Clinical Presentation, Survival Outcomes, and Treatment Trends—A Long-Term Follow-Up Study - Joekim, Jason Fernandes; RC, Subhoth; Shetty, Nishitha; Shet, Dinesh (Indian Journal of Medical and Paediatric Oncology, 2025)
Duodenal adenocarcinoma (DA) is a rare and aggressive malignancy, representing less than 0.5% of all gastrointestinal cancers. It constitutes a significant portion (55.7%) of small bowel adenocarcinomas, most of which arise in the second part of the duodenum, followed by the third and fourth parts. Despite its rarity, DA presents substantial challenges in diagnosis and treatment due to its aggressive nature and often insidious onset.The aim of the study is to investigate the clinical presentation, prognostic factors, survival outcomes, and treatment strategies in DA, with a focus on surgical and adjuvant therapeutic interventions. Additionally, the study aims to elucidate patterns of recurrence and identify areas for future research to optimize therapeutic approaches and enhance patient care.This retrospective observational study (2015–2023) analyzed patients aged 18 to 90 years with DA. Data from case sheets, laboratory investigations, and medication charts were reviewed. This study aims to explain demographic characteristics, clinical presentations, treatment trends, and survival outcomes to improve therapeutic strategies and patient care in DA patients, excluding other gastrointestinal cancersThe study examined 10 cases of DA diagnosed between 2015 and 2023. The patient cohort had an equal gender distribution, with ages ranging from 53 to 83 years. Chief presenting symptoms included abdominal pain (90%) and vomiting (50%). Tumor markers were elevated in 40% of patients. Tumor locations predominantly included the D2 region. Three patients underwent Whipple's surgery and three received chemotherapy with curative intent.The study highlights the challenges associated with DA, including its rare incidence, clinical presentations, and variable treatment outcomes. Surgical interventions such as the Whipple procedure and adjuvant chemotherapy show promise in improving survival rates. Further studies with larger cohorts are essential to better understand the disease, refine therapeutic strategies formulate separate guidelines for DA, and enhance patient outcomes.N/A.
Keywords: duodenal adenocarcinoma; gastrointestinal malignancies; small bowel cancer